(untitled) (Zaporizhzhia Historical Review, 2021)
Gradual revival of the Ukrainian people religiousness was determined by the interest to the history of different religious organizations activity which exist in Ukraine. Roman-Catholicism occupies the essential place among them. Under the influence of changes in the political life of Ukraine the problem of church activity is very actual in the modern historical science and it has been opened for the greater audience. But it is necessary to remark that the detailed analysis of the scientific condition of development of the characteristic of the RomanCatholics activity in the south of Ukraine allows to attribute it to the problems of the Ukrainian historical science which is in progress, these researches will essentially deepen our ideas about the history of religious life of Ukraine and religiousness features.